Web-based public complaints information system for Subang City - Emy Lenora Tatuhey; Tukino; Irpan Hilmi (Information System; Universitas Buana Perjuangan Karawang, 2022)
The media currently limit public complaints, and some people find it difficult to convey or report events in the area. Complaints are still not fully using information technology media. This makes it difficult for the public to provide suggestions or submit complaints. The authors developed an information system for the public complaint process using the waterfall method from these problems. This system aims to create a Jatibaru village website and create a complaint website for the community so that complaints in the community can be conveyed properly through the complaints website. The public can review the complaints to determine whether the complaints have been processed or not. System development using the PHP and HTML programming languages. The final result of this study resulted in a public complaint information system so that the aspirations of the community were properly conveyed to the village government, all complaints would be discussed by the village apparatus to minimize complaints from the community, and with this system, it can also help monitor complaints submitted by the community.